KONTRIBUSI PELATIHAN DALAM MENDUKUNG KINERJA SALES REPRESENTATIVE MERCHANT (SRM) DI PERBANKAN - Nur Aini Fathmawati (Journal of Business & Banking, 2014)
Training activity is the main important activity for improving human resources competences inany organization, including in banking industry. Training enables company in reducing gap ofthe companys requirements and human resources qualification. In order achieving trainingeffectiveness, training should be design fit in with organization need analysis, and mentionmany factors related with training activity such as the contents of Training Materials, TrainingFacilities, Trainers and Training methods. The purpose of this study was to examine the effectsimultaneously and partially of training success determinants factors on performance of SalesRepresentative Merchant (SMR) in bank X. Research conducted by survey design and usingquestionnaires research which involved 81 Sales Representative who participate in Sales Merchanttraining. Multiple regression analysis used as tool for analyzing data. The results foundthat all determinants training success factors have significantly effects simultaneously and partiallyon sales representative performance. The content of material has dominant effects onsales performance. The implication of this research is bank should consider the relevancy ofTraining Materials, Training Facilities, Trainers, and Methods for designing training program.